Long‐Term High‐Intensity Interval Training Intervention Improves Emotional Conflict Control in Association With Right Ventrolateral Prefrontal Activation in Males With Methamphetamine Use Disorder: A Randomized Controlled Trial - He, Meiheng; Wang, Lili; Xu, Ding; Liu, Ying; Zhu, Xiangru; Zhu, Dong; Yang, Suyong (Scandinavian journal of medicine & science in sports, 2024)
ABSTRACT Acute high‐intensity interval training (HIIT) has cognitive benefits in individuals with methamphetamine use disorder (MUD), yet it remains largely unknown the benefits of long‐term HIIT on emotional conflict control and its neural mechanism in individuals with MUD. The current study conducted a 36‐week low‐volume HIIT intervention to investigate the effects of HIIT on emotional conflict control in males with MUD and their prefrontal cortex (PFC) activation. This study was a sub‐study of the Study for Rehabilitation Training Model Construction and Training Effect of High Intensity Compound Exercise Prescription. Forty males with MUD (31.50 ± 4.33 years) were randomly assigned to the HIIT group and control group. The HIIT group received a 36‐week low‐volume HIIT intervention, while the control group maintained daily physical exercise. The emotional conflict task (emotional face‐word Stroop task) with functional near‐infrared spectroscopy (fNIRS) recording and subjective craving test were performed before and after the intervention. The results showed that the HIIT intervention reduced the emotional conflict and increased cortical activations of right dorsolateral PFC (dlPFC) and right ventrolateral PFC (vlPFC). More importantly, the HIIT‐induced decreased emotional conflict was associated significantly with increased right vlPFC activation. In addition, subjective craving was also reduced after HIIT intervention. While the control group showed significant changes in neither brain activation nor the craving. These findings suggest that long‐term low‐volume HIIT can improve PFC activation, promote emotional conflict control, and reduce subjective craving in males with MUD. HIIT seems to be an effective method of withdrawal rehabilitation for males with MUD.